Effect of gut stress induced by oxidized wheat gluten on the growth performance, gut morphology and oxidative states of broilers. Issue 2 (11th January 2018) - Liao, R. B.; Yan, H. J.; Liu, G. H.; Zhang, S.; Chang, W. H.; Liu, W.; Lin, C. H.; Huang, X. Y.; Cai, H. Y.
Summary: This study was to investigate the effect of oxidized wheat gluten (OG) on growth performance, gut morphology and its oxidative states of broilers. One hundred and eighty‐day‐old male broilers (10 chicks/pen) were randomly allocated into three dietary treatments: control diet (CON), diet with 8% wheat gluten (WG) and diet with 8% OG with six pens/treatment. Body weight (BW) (21 and 35 days) and average daily gain (ADG) (1–21 days and 22–35 days) decreased ( p  < .05) and feed conversion ratio (FCR) (1–21 days and 22–35 days) increased ( p  < .05) in OG treatment. Feed intake (FI) decreased ( p  < .05) in WG and OG treatments during 22–35 days. However, FI was not influenced by dietary treatments during 1–21 days ( p  > .05). The OG‐fed broilers had a lower faecal pH value ( p  < .05) and higher faecal moisture content ( p  < 05) at 14, 21, 28 and 35 days. Villus height, crypt depth and V/C value were not different ( p  > .05) among treatments at 21 and 35 days. Lipid peroxidation (LPO) (21 and 35 days) and malondialdehyde (MDA) (35 days) content in crop of OG treatment increased ( p  < .05). Oxidized glutathione (GSSG) (21 days), LPO (21 and 35 days) and MDA (21 and 35 days) content in ileum of OG treatment increased ( p  < .05). The reduced glutathione/oxidized glutathione (GSH/GSSG) (21 days) and (GSH) (35 days) in ileum of OG treatment decreased ( p  < .05). The present findings indicate that OG might be a stressor for broiler gut, which could induce oxidative stress both in crop and in ileum, and the diarrhoea as well. The growth performance of broiler was consequently depressed.